European Film Remakes - Cuelenaere, Eduard (Screen Serialities : SCSE, 2022)
Combines historical and contemporary approaches to film remakes in EuropeInvestigates, next to the textual, socio-cultural and political dimensions, the often neglected industrial, financial and production-related dynamics of European remake practicesProvides a mix of different methodologies, ranging from comparative textual analysis to production, promotion, and reception analysisTakes into account both popular and art cinema remakesExamines European film remakes within local, regional, national, transnational or transcultural contextsOffers new theoretical concepts and methodological models that take into account both the distinctive and universal aspects of film remaking in a European contextBringing together a range of international scholars, European Film Remakes discusses for the first time the textual, socio-cultural, political, and industrial mechanisms and singularities of the film remake in a European context. Offering a variety of historical, theoretical, and methodological approaches, the book is illustrated by a wide range of case studies from across Europe, including films like A Bigger Splash, Open Your Eyes and Perfect Strangers. Although commonly understood as a typical Hollywood practice, this book demonstrates how film remakes are, and always have been, a significant part of the European film culture and industry